Sonidegib reduced tumor burden in patients with advanced basal cell carcinoma in the BOLT trial: Long-term analysis results - Michael R. Migden; Aaron S. Farberg; James Spencer; Felix Kiecker; Alexander Guminski; Kurt Gebauer; Carmen Loquai; Caroline Robert; Reinhard Dummer; Dirk Schadendorf; Axel Hauschild; Jean Jacques Grob; et al. (EJC Skin Cancer)
Background: The Hedgehog inhibitor sonidegib had durable efficacy and a manageable safety profile in patients with locally advanced basal cell carcinoma (laBCC) through 42 months of the BOLT trial. In this analysis, we characterize the effects of 200-mg and 800-mg sonidegib on tumors in patients in the BOLT trial. Methods: Tumors were assessed using color photography and magnetic resonance imaging (MRI) by central and investigator review at baseline; Weeks 5, 9, and 17 after the start of treatment; then every 8 weeks during the first year; and every 12 weeks thereafter. Results: In patients with laBCC receiving sonidegib, the decrease in best percentage change from baseline in target lesions was 92.3 % per central review and 96.7 % per investigator review in the 200-mg treatment arm, and 90.1 % per central review and 95.2 % per investigator in the 800-mg treatment arm. The kinetics of response to treatment appeared to influence tumor reduction, with patients responding within the first 3 months of treatment experiencing a greater decrease in tumor size over time than later responders. Additionally, patients whose best overall response to treatment was complete response or partial response had a generally longer duration of response compared with patients who had stable disease as best overall response. Tumor reduction and duration of response were greater when assessed by investigator review compared with central review. Conclusion: Treatment with sonidegib for up to 42 months substantially reduced tumors in patients with laBCC.